The Role of Advanced Computation, Predictive Technologies, and Big Data Analytics in Food and Nutrition Research: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2024)
Artificial intelligence (AI), machine learning (ML), and deep learning (DL) are promising tools that can be used to develop algorithms to better understand and predict interactions between food- and nutrition-related data and health outcomes. Understanding that additional research is needed to identify areas where AI\/ML is likely to have an impact, the National Academies Food and Nutrition Board hosted a public workshop in October 2023 to explore the future benefits and limitations of integrating big data and AI\/ML tools into nutrition research. Participants also discussed issues related to diversity, equity, inclusion, bias, and privacy and the appropriate use of evidence generated from these new methods.

The Role of Advanced Computation, Predictive Technologies, and Big Data Analytics Related to Food and Nutrition Research: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2024)
The National Academies Food and Nutrition Board hosted a hybrid public workshop in October 2023 to explore opportunities and challenges related to applying advanced computation, big data analytics, and high-performance computing, including artificial intelligence, machine learning, and deep learning, to support advances in food systems and nutrition research. Speakers discussed the appropriate use of evidence generated from these methods to inform food- and nutrition-related programs and policies.

Sustainability Considerations for Procurement Tools and Capabilities: Summary of a Workshop - National Research Council (The National Academies Press, 2012)
Federal laws, regulations, and executive orders have imposed requirements for federal agencies to move toward the sustainable acquisition of goods and services, including the incorporation of sustainable purchasing into federal agency decision making. Since the federal government is such a significant player in the market, its move to incorporate sustainable procurement practices could have a profound impact on the types of products being developed for the market as a whole. The General Services Administration (GSA) has played a key role in furthering sustainable procurement practices throughout the federal government. GSA is responsible for formulating and maintaining government-wide policies covering a variety of administrative actions, including those related to procurement and management. GSA has several ongoing activities related to sustainable procurement to assess the feasibility of working with the federal supplier community - vendors and contractors that serve federal agencies to measure and reduce greenhouse gas emissions in the supply chain while encouraging sustainable operations among suppliers. GSA has also been actively developing programs to assist federal agencies in making sustainable procurement decisions. As federal agencies cannot directly fund the development of sustainable procurement tools, they are particularly interested in understanding how to foster innovation and provide incentives for collaboration between developers and users of tools for sustainable purchasing throughout the supply chain. The training of procurement professionals is also a priority for these agencies. To assist efforts to build sustainability considerations into the procurement process, the National Research Council appointed a committee to organize a two-day workshop that explored ways to better incorporate sustainability considerations into procurement tools and capabilities across the public and private sectors. The workshop was designed to help participants assess the current landscape of green purchasing tools, identify emerging needs for enhanced or new tools and opportunities to develop them, identify potential barriers to progress, and explore potential solutions. The workshop provided an opportunity for participants to discuss challenges related to sustainable purchasing and to developing new procurement tools. Sustainability Considerations for Procurement Tools and Capabilities reviews the presenters' recommendations and tools currently used in sustainable procurement, such as databases for ecolabels and standards, codes, or regulations and other nontechnological tools such as policies, frameworks, rating systems, and product indexes.

The Case for International Sharing of Scientific Data: A Focus on Developing Countries: Proceedings of a Symposium - National Research Council (The National Academies Press, 2012)
The theme of this international symposium is the promotion of greater sharing of scientific data for the benefit of research and broader development, particularly in the developing world. This is an extraordinarily important topic. Indeed, I have devoted much of my own career to matters related to the concept of openness. I had the opportunity to promote and help build the open courseware program at the Massachusetts Institute of Technology (MIT). This program has made the teaching materials for all 2,000 subjects taught at MIT available on the Web for anyone, anywhere, to use anytime at no cost. In countries where basic broadband was not available, we shipped it in on hard drives and compact disks. Its impact has been worldwide, but it has surely had the greatest impact on the developing world. I am also a trustee of a nonprofit organization named Ithaca that operates Journal Storage (JSTOR) and other entities that make scholarly information available at very low cost. The culture of science has been international and open for centuries. Indeed, the scientific enterprise can only work when all information is open and accessible, because science works through critical analysis and replication of results. In recent years, as some scientific data, and especially technological data, have increased in economic value frequently has caused us to be far less open with information than business and free enterprise require us to be. Indeed, the worldwide shift to what is known as open innovation is strengthening every day. Finally, since the end of World War II, the realities of modern military conflict and now terrorism have led governments to restrict information through classification. This is important, but I believe that we classify far too much information. The last thing we need today, at the beginning of the twenty-first century, is further arbitrary limitations on the free flow of scientific information, whether by policies established by governments and businesses, or by lack of information infrastructure. For all these reasons, the international sharing of scientific data is one of the topics of great interest here at the National Academies and has been the subject of many of our past reports. This is the primary reason why this symposium has been co-organized by the NRC's Policy and Global Affairs Division2014the Board on International Scientific Organizations (BISO) and the Board on Research Data and Information (BRDI). The Case for International Sharing of Scientific Data: A Focus on Developing Countries: Proceedings of a Symposium summarizes the symposium.

Computers, Communications, and Public Policy: Report of a Workshop at Woods Hole, Massachusetts, August 14-18, 1978 - National Research Council (The National Academies Press, 1981)

Computing, Communication, and the Information Age - John E. Hopcroft (The National Academies Press, 1994)

Critical Issues in NASA Information Systems: Final Report to the National Aeronautics and Space Administration (The National Academies Press, 1987)

Computing Research for Sustainability - National Research Council
A broad and growing literature describes the deep and multidisciplinary nature of the sustainability challenges faced by the United States and the world. Despite the profound technical challenges involved, sustainability is not, at its root, a technical problem, nor will merely technical solutions be sufficient. Instead, deep economic, political, and cultural adjustments will ultimately be required, along with a major, long-term commitment in each sphere to deploy the requisite technical solutions at scale. Nevertheless, technological advances and enablers have a clear role in supporting such change, and information technology (IT) is a natural bridge between technical and social solutions because it can offer improved communication and transparency for fostering the necessary economic, political, and cultural adjustments. Moreover, IT is at the heart of nearly every large-scale socioeconomic system-including systems for finance, manufacturing, and the generation and distribution of energy-and so sustainability-focused changes in those systems are inextricably linked with advances in IT. The focus of Computing Research for Sustainability is \

Global Networks and Local Values: A Comparative Look at Germany and the United States - National Research Council (The National Academies Press, 2001)
Whether you call it the third wave, the information revolution, or the virtually connected world, the implications of a global information network are profound. As a society, we want to forestall the possible negative impacts without closing the door to the potential benefits. But how? Global Networks and Local Values provides perspective and direction, focusing on the relationship between global information networks and local values-that is, the political, economic, and cultural norms that shape our daily lives. This book is structured around an illuminating comparison between U.S. and German approaches toward global communication and information flow. (The United States and Germany are selected as two industrialized, highly networked countries with significant social differences.) Global Networks and Local Values captures the larger context of technology and culture, explores the political and commercial institutions where the global network functions, and highlights specific issues such as taxation, privacy, free speech, and more. The committee contrasts the technical uniformity that makes global communication possible with the diversity of the communities being served and explores the prospects that problems resulting from technology can be resolved by still more technology. This thoughtful volume will be of interest to everyone concerned about the social implications of the global Internet.

Avoiding Surprise in an Era of Global Technology Advances - National Research Council (The National Academies Press, 2005)
The global spread of science and technology expertise and the growing commercial access to advanced technologies with possible military application are creating potentially serious threats to the technological superiority underpinning U.S. military strength. Key to dealing with this situation is the ability of the U.S. intelligence community to be able to provide adequate and effective warning of evolving, critical technologies. To assist in performing this task, the Technology Warning Division of the Defense Intelligence Agency (DIA) asked the National Research Council (NRC) to undertake a study examining technology warning issues. This report provides the first part of that study. It presents an assessment of critical, evolving technologies; postulates ways potential adversaries could disrupt these technologies; and provides indicators for the intelligence community to determine if such methods are under development. The intention of this report is to establish the foundation for a long-term relationship with the technology warning community to support the examination of technology warning issues.

The Internet Under Crisis Conditions: Learning from September 11 - National Research Council (The National Academies Press, 2003)
This report presents findings of a workshop featuring representatives of Internet Service Providers and others with access to data and insights about how the Internet performed on and immediately after the September 11 attacks. People who design and operate networks were asked to share data and their own preliminary analyses among participants in a closed workshop. They and networking researchers evaluated these inputs to synthesize lessons learned and derive suggestions for improvements in technology, procedures, and, as appropriate, policy.

Software for Dependable Systems: Sufficient Evidence? - National Research Council (The National Academies Press, 2007)
The focus of Software for Dependable Systems is a set of fundamental principles that underlie software system dependability and that suggest a different approach to the development and assessment of dependable software. Unfortunately, it is difficult to assess the dependability of software. The field of software engineering suffers from a pervasive lack of evidence about the incidence and severity of software failures; about the dependability of existing software systems; about the efficacy of existing and proposed development methods; about the benefits of certification schemes; and so on. There are many anecdotal reports, which2014although often useful for indicating areas of concern or highlighting promising avenues of research2014do little to establish a sound and complete basis for making policy decisions regarding dependability. The committee regards claims of extraordinary dependability that are sometimes made on this basis for the most critical of systems as unsubstantiated, and perhaps irresponsible. This difficulty regarding the lack of evidence for system dependability leads to two conclusions: (1) that better evidence is needed, so that approaches aimed at improving the dependability of software can be objectively assessed, and (2) that, for now, the pursuit of dependability in software systems should focus on the construction and evaluation of evidence. The committee also recognized the importance of adopting the practices that are already known and used by the best developers; this report gives a sample of such practices. Some of these (such as systematic configuration management and automated regression testing) are relatively easy to adopt; others (such as constructing hazard analyses and threat models, exploiting formal notations when appropriate, and applying static analysis to code) will require new training for many developers. However valuable, though, these practices are in themselves no silver bullet, and new techniques and methods will be required in order to build future software systems to the level of dependability that will be required.

Building an Electronic Records Archive at the National Archives and Records Administration: Recommendations for a Long-Term Strategy - National Research Council (The National Academies Press, 2005)
The federal government generates and increasingly saves a large and growing fraction of its records in electronic form. In 1998, the National Archives and Record Administration (NARA) launched its Electronic Archives (ERA) program to create a system to preserve and provide access to federal electronic records. To assist in this project, NARA asked the NRC to conduct a two-phase study to provide advice as it develops the ERA program. The first two reports (phase one) provided recommendations on design, engineering, and related issues facing the program. This report (phase two) focuses on longer term, more strategic issues including technology trends that will shape the ERA system, archival processes of the ERA, and future evolution of the system. It also provides an assessment of technical and design issues associated with record integrity and authenticity.

Identification of Research Needs Relating to Potential Biological or Adverse Health Effects of Wireless Communication Devices - National Research Council (The National Academies Press, 2008)
In recent years there has been a rapid increase in the use of wireless communications devices and a great deal of research has been carried out to investigate possible biological or human health effects resulting from their use. The U.S. Food and Drug Administration asked the National Research Council to organize a workshop to identify research needs and gaps in knowledge in the areas of dosimetry and exposure, epidemiology, human laboratory studies, mechanisms, and animal and cell biology. The workshop did not include the evaluation of health effects or the generation of recommendations relating to how identified research needs should be met. Some needs and gaps identified at the workshop include: (1) characterization of exposures from wireless devices and RF base station antennas in juveniles, children, fetuses, and pregnant women and (2) evaluation of devices that use newer technologies (e.g., texting, web-surfing).

Computing and Communications in the Extreme: Research for Crisis Management and Other Applications - National Research Council (The National Academies Press, 1996)
This book synthesizes the findings of three workshops on research issues in high-performance computing and communications (HPCC). It focuses on the role that computing and communications can play in supporting federal, state, and local emergency management officials who deal with natural and man-made hazards (e.g., toxic spills, terrorist bombings). The volume also identifies specific research challenges for HPCC in meeting unmet technology needs in crisis management and other nationally important application areas, such as manufacturing, health care, digital libraries, and electronic commerce and banking.

Getting Up to Speed: The Future of Supercomputing - National Research Council (The National Academies Press, 2005)
Supercomputers play a significant and growing role in a variety of areas important to the nation. They are used to address challenging science and technology problems. In recent years, however, progress in supercomputing in the United States has slowed. The development of the Earth Simulator supercomputer by Japan that the United States could lose its competitive advantage and, more importantly, the national competence needed to achieve national goals. In the wake of this development, the Department of Energy asked the NRC to assess the state of U.S. supercomputing capabilities and relevant R&D. Subsequently, the Senate directed DOE in S. Rpt. 107-220 to ask the NRC to evaluate the Advanced Simulation and Computing program of the National Nuclear Security Administration at DOE in light of the development of the Earth Simulator. This report provides an assessment of the current status of supercomputing in the United States including a review of current demand and technology, infrastructure and institutions, and international activities. The report also presents a number of recommendations to enable the United States to meet current and future needs for capability supercomputers.

A 21st Century Cyber-Physical Systems Education - National Academies of Sciences, Engineering,; Medicine
Cyber-physical systems (CPS) are \

An Assessment of the Communications Technology Laboratory at the National Institute of Standards and Technology: Fiscal Year 2019 - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
An Assessment of the Communications Technology Laboratory at the National Institute of Standards and Technology: Fiscal Year 2019 is an independent technical assessment of the quality of the National Institute of Standards and Technology's (NIST's) Communications Technology Laboratory (CTL). It reviews the organization's technical programs, the portfolio of scientific expertise within the organization, the adequacy of the organization's facilities, equipment, and human resources, and the effectiveness by which the organization disseminates its program outputs. This report focuses on CTL priority areas such as public safety communications, trusted spectrum testing, and Next Generation Wireless (5G and Beyond). It also assesses the extent to which CTL applied the recommendations from a 2015 National Academies' report, which describes many of the critical uses of radio communications, provides lab-specific recommendations, and highlights important research priorities for the Boulder, Colorado communications technology laboratory of the Department of Commerce laboratory. This new report also describes the current activities of the Boulder telecommunications laboratories, its strengths and weaknesses as an organization, and its plans for the near future

Exploring Encryption and Potential Mechanisms for Authorized Government Access to Plaintext: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
In June 2016 the National Academies of Sciences, Engineering, and Medicine convened the Workshop on Encryption and Mechanisms for Authorized Government Access to Plaintext. Participants at this workshop discussed potential encryption strategies that would enable access to plaintext information by law enforcement or national security agencies with appropriate authority. Although the focus of the workshop was on technical issues, there was some consideration of the broader policy context, and discussion about the topics of encryption and authorized exceptional analysis frequently addressed open policy questions as well as technical issues. This publication summarizes the presentations and discussions from the workshop.

Summary of a Workshop on Software-Intensive Systems and Uncertainty at Scale - National Research Council (The National Academies Press, 2007)